Strength and conditioning considerations for female mixed martial artists - Schick, M.; Brown, L.; Schick, E. E. (Strength and Conditioning Journal, 2012)
Mixed martial arts (MMA) is a combat sport that combines Brazilian jiu-jitsu (bjj), muay thai kickboxing, and wrestling. Athletic performance can be enhanced by the application of a training program specific to MMA, which is a physically demanding activity that uses both anaerobic and aerobic energy systems. There is no peer-reviewed research regarding the best possible training methods for a female MMA fighter. This article will assess the physiological demands of MMA, examine the needs of female combat athletes, discuss peer-reviewed research about combat sport training methods, and suggest proper sport-specific training structures that will optimize performance and reduce the risk of injury. Volltext: http://faculty.fullerton.edu/leebrown/PDF%20Files/Theses/Schick-Strength%20and%20conditioning%20for%20female%20MMA.pdf